2021
DOI: 10.1097/bpo.0000000000001896
|View full text |Cite
|
Sign up to set email alerts
|

What Is New in Pediatric Bone Health

Abstract: Background: This review paper aims to report on the last 5 years of relevant research on pediatric bone health in regard to nutrition and obesity, ethnic disparities, common orthopaedic conditions, trauma, spine, and sports medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…In the literature, due to differences in data from countries, the level of vitamin D in children and adolescents varies between 19% and 60%, and the level of deficiency varies between 7% and 68% [ 26 ]. Studies have shown that patients with musculoskeletal pain may have D hypovitaminosis, and hypovitaminosis D may cause widespread chronic musculoskeletal pain, particularly chronic low back pain [ 13 , 27 - 29 ]. Vitamin D is a hormone that regulates calcium and bone metabolism and is important in the inflammatory and immune response of the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, due to differences in data from countries, the level of vitamin D in children and adolescents varies between 19% and 60%, and the level of deficiency varies between 7% and 68% [ 26 ]. Studies have shown that patients with musculoskeletal pain may have D hypovitaminosis, and hypovitaminosis D may cause widespread chronic musculoskeletal pain, particularly chronic low back pain [ 13 , 27 - 29 ]. Vitamin D is a hormone that regulates calcium and bone metabolism and is important in the inflammatory and immune response of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with musculoskeletal pain may have D hypovitaminosis, and hypovitaminosis D may cause widespread chronic musculoskeletal pain, particularly chronic low back pain [13,[27][28][29]. Vitamin D is a hormone that regulates calcium and bone metabolism and is important in the inflammatory and immune response of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a distinctive NAFLD-associated transcriptomic signature, which included a highly expressed TGF-β1, has been reported in the white AT of severely obese females [ 16 ]. Besides vascular inflammation, weight gain, kidney failure, and liver and heart diseases, the disease–gene interaction also revealed unipolar depression, various cancers, and scoliosis, all known risks for obese children [ 3 , 20 , 21 ]. Several cancer-related TFs such as JUNB, JUND, Forkhead box protein M1 (FOXM1), and ETS1 were part of the TF–mRNA regulatory network.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric bone health is influenced by many factors, including nutrition, obesity, and systemic health conditions that can contribute to fracture rate and the need for treatment among pediatric patients [ 26 ]. Our study found that patients from URM groups were more likely to have higher ASA scores and pulmonary comorbidities.…”
Section: Discussionmentioning
confidence: 99%